2015
DOI: 10.1007/s10243-015-0406-2
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of concurrent chronic insertional Achilles tendinosis and chronic midsubstance Achilles tendinosis with Haglund deformity: A case report

Abstract: Achilles tendinopathy affects athletes at all levels. While tendinopathy is usually found in either the midsubstance or the Achilles insertion, it is rarely seen in both areas of the tendon concomitantly. We report on a rare case of bilateral chronic insertional Achilles tendinosis and chronic midsubstance Achilles tendinosis with Haglund deformity treated with central tendon debridement, flexor hallucis longus (FHL) transfer, Haglund resection, and reattachment of the Achilles insertion using the Arthrex Spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…They reported that 42 of 43 patients returned to their activities of daily living, including running in 20 athletic patients (100%). Other reports also demonstrated the efficacy of this new technique (4,6). In a biomechanical study, Pilson et al reported that they did not find a statistically significant difference in the peak load to failure between the conventional suture…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…They reported that 42 of 43 patients returned to their activities of daily living, including running in 20 athletic patients (100%). Other reports also demonstrated the efficacy of this new technique (4,6). In a biomechanical study, Pilson et al reported that they did not find a statistically significant difference in the peak load to failure between the conventional suture…”
Section: Discussionmentioning
confidence: 94%
“…insertion securely fixed the tendon to the prepared bony surface. The interference screw fixation eliminated the need for a series of bulky knots at the repair site (6). Then, simple interrupted sutures with 4-0 PDS were used to approximate the incised area of the Achilles tendon and paratenon.…”
Section: The Journal Of Medical Investigation Vol 63 August 2016mentioning
confidence: 99%
See 1 more Smart Citation